Advance and Emerging Roles of Hydrogel in Promoting Periodontal Tissue Regeneration and Repairing Bone Defect - Singh, Harshdeep; Rebello, Pawan; Puthenkandathil, Rahul; Vyas, Dhwani; Chavda, Jahanvi; Gajdhar, Sajda Khan (Journal of Neonatal Surgery, 2025)
Aim: This study was conducted to investigate the role of hydrogel on alveolar bone defect repairment of bone defect and promoting periodontal tissue Regeneration Methods: For this clinical study, we recruited 23 patients (17 females and 6 males with a mean age of 50.3 years) who had moderate to advanced chronic periodontitis. Compromised systemic health condition and no contraindications for periodontal surgery . All study subjects had destruction of periodontal tissue and at least one 1-, 2- or 3-walled bone defect. Before periodontal surgical treatment, each patient received an initial preparatory session, including oral hygiene instruction, scaling, and root planing. Results: The pre-treatment and post-treatment clinical parameters were evaluate and we compared the values of PPD, CAL, and LBG at 3, 6, and 12 months after treatment with the pre-treatment values. From before treatment to 12 months after treatment, the changes in mean PPD and mean CAL of treated sites were 3.8 ± 1.9 mm and 5.9 ± 2.0 mm, respectively. Also, at 12 months following treatment, hard tissue showed a mean LBG of 3.5 ± 2.1 mm and a mean BF of 61.8 ± 25.2%. The mean depth of bone defects and periodontal tissue regeneration was less at both 6 months and 12 months compared with the pre-treatment mean . These differences were statistically significant Conclusion: The results demonstrated that the hydrogel successfully delivered periodontal ligament stem cells derived exosomes for repairing alveolar bone defects . We evaluated the clinical effects of the sustained release of bFGF from gelatin hydrogel for the treatment of periodontal disease with infrabony defects and periodontal tissue regeneration . we obtain clinical attachment gain, probing depth reduction, and radiographic bone fill. We conclude by suggesting that the topical application of gelatin hydrogel in the treatment of chronic periodontitis with infrabony defects or furcation is safe, leads to improvement of clinical parameters, and offers promise as a new avenue for periodontal regeneration.